Reliable and efficient operation of distribution network by connecting solar distributed generation - Simarla Vijender Reddy; Mane Manjula (Institute of Advanced Engineering and Science, 2023)
One of the major issues in the distribution network (DN) is ensuring that power systems operate optimally in light of the effects of distributed generation (DG). In a broader sense, optimal operation in a power system refers to the most efficient use of all active and reactive power generation and control equipment that adheres to physical and technical constraints. Most studies focused on DG size and location in the DN, using various optimization techniques for loss reduction. But in a practical distribution network, reliable operation is dependent on the demand and power supply at any given moment. Solar DGs provide variable power throughout the day, and loads are similarly variable. It is difficult for the DN to function efficiently and reliably while handling variable loads and DG power supplies. Voltages and power losses are measured as loads change by connecting solar DGs to assess the performance of the DN.